'A mere gutter!' The Carioca Aqueduct and water delivery in mid-nineteenth-century Rio de Janeiro. (February 2022) - Metcalf, Alida C.; Smith, Sean Morey; Kennedy, S. Wright
Abstract: The two key aspects of water infrastructure – engineered and human – in mid-nineteenth-century Rio de Janeiro are the foci of this article. On the one hand, gravity flow engineering brought fresh water from the Tijuca Forest to the fountains in the city, but on the other, hundreds of slaves carried heavy jugs of water from the fountains though the streets to residences. Using the account of Thomas Ewbank (1856), georeferenced historical maps and a field study, this article first reconstructs the route of the Carioca Aqueduct, then, using the accounts of Ewbank and other travellers, turns to the delivery of water in the city by enslaved water carriers.